Reliability of the Turkish version of the European Obstructive Sleep Apnea Screening (EUROSAS) questionnaire for drivers - ÖZAYDIN, AYŞE NİLÜFER (SPRINGER HEIDELBERG, 2021)
Purpose The European Union Driver License Committee recently developed a questionnaire as a screening tool for obstructive sleep apnea (OSA) named the European Obstructive Sleep Apnea Screening (EUROSAS) questionnaire for drivers. We sought to address the reliability of the Turkish version of this questionnaire. Methods The EUROSAS was translated into Turkish. Using a test-retest approach, data were collected twice with a 15-day interval among 150 participants (50 professional male drivers [PMD], 50 non-professional male drivers [NPMD], and 50 non-professional female drivers [NPFD]). The EUROSAS score ranges between 2 and 25, with scores >= 10 suggesting the presence of OSA. Results The median EUROSAS scores in the first test were 8.0 (interquartile range [IQR] 6.8-12.0) in PMD, 8.0 (IQR 6.0-11.0) in NPMD, and 5.0 (IQR 4.0-8.0) in NPFD (p< 0.001). Corresponding values in the retest were 9.5 (IQR 7.0-13.0), 8.0 (IQR 6.0-10.0), and 5.0 (IQR 4.0-8.0), respectively (p< 0.001). The EUROSAS score >= 10 was found among 34% in the first test and 50% in the retest in PMD (ns), 34% vs 24% in NPMD (ns), and 8% vs 16% in NPFD (ns). There was a positive correlation between the tests (r= 0.864,p< 0.001), and Cronbach's alpha value for the whole group was 0.477 (0.514 for PMD, 0.512 for NPMD, and 0.543 NPFD, respectively). Conclusions The EUROSAS-Turkish version is easy to understand and is reproducible. However, the test-retest reliability level is poor among the Turkish drivers. Further validation of the questionnaire by objective sleep studies and fitness-to-drive testing is necessary.
Keywords: Obstructive sleep apnea; Traffic safety; Daytime sleepiness; Questionnaire; DRIVING RISK